Quantum model for the effect of thiols adsorption on resistivity of gold ultrathin films - Ricardo Henríquez; Claudio Gonzalez-Fuentes; Valeria del Campo; Jonathan Correa-Puerta; Carolina Parra; Francisca Marín; Patricio Häberle (Results in Physics, 2019)
The predominant role of surface scattering, in electronic transport through nanoscale thin films, was examined by measuring and modeling the change in resistivity induced by the adsorption of thiols on the surface. For this purpose, gold ultrathin films on sapphire, using chromium as surfactant, were prepared through thermal evaporation, seeking to maximize the surface induced dispersion. A maximum resistivity increase of 13.5% was observed, in an 8 nm Au/Cr/Sapphire sample. This is the highest reported value for such films to date. The morphology of the samples was measured by STM and characterized through height-difference correlation function. A fractal self-affine representation of the surface was found, and it was modified to account the thiol effect: the scattering center due to the adsorption of a molecule was modeled as a void in the surface. This change was related to the electrical transport of the film through two quantum models: the Palasantzas and Barnas (PB) theory and the Sheng, Xing and Wang theory, extended by Munoz et al. (mSXW). For our samples, the mSXW theory did not predict a resistivity change, while the PB theory provides a good description of the experimental resistivity increase due to thiols adsorption as function of thickness. Keywords: Electrical resistivity, Fractal description, Thiols, Ultra thin films, Coating